Anticomplementary activity in serum samples from patients with acute parvovirus B19 infection. Issue 5 (May 1995) - Barton, S A; Nash, J Q; Jones, J; Sillis, M; Cohen, B J
Abstract : Of 65 serum samples submitted for diagnostic purposes which proved to be anti-complementary by complement fixation test, 49 were parvovirus B19 IgM positive. Forty four of the 49 serum samples were from patients with arthropathy. Acute parvovirus B19 infection should be suspected when a patient has symptoms of disease of the joints and the serum is anticomplementary.